Bioengineered protein-based nanocage for drug delivery - Lee, Eun Jung; Lee, Na Kyeong; Kim, In-San (ELSEVIER SCIENCE BV, 2016)
Nature, in its wonders, presents and assembles the most intricate and delicate protein structures and this remarkable phenomenon occurs in all kingdom and phyla of life. Of these proteins, cage-like multimeric proteins provide spatial control to biological processes and also compartmentalizes compounds that may be toxic or unstable and avoids their contact with the environment Protein-based nanocages are of particular interest because of their potential applicability as drug delivery carriers and their perfect and complex symmetry and ideal physical properties, which have stimulated researchers to engineer, modify or mimic these qualities. This article reviews various existing types of protein-based nanocages that are used for therapeutic purposes, and outlines their drug-loading mechanisms and bioengineering strategies via genetic and chemical functionalization. Through a critical evaluation of recent advances in protein nanocage-based drug delivery in vitro and in vivo, an outlook for de novo and in silico nanocage design, and also protein-based nanocage preclinical and future clinical applications will be presented. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: VIRUS-LIKE PARTICLES; COWPEA MOSAIC-VIRUS; SUPRAMOLECULAR BUILDING-BLOCKS; DENDRITIC CELL ACTIVATION; HORSE SPLEEN APOFERRITIN; HEAT-SHOCK-PROTEIN; VIRAL NANOPARTICLES; CAGE NANOPARTICLES; TARGETED DELIVERY; IN-VITRO